TRANSIT ORIENTED DEVELOPMENT (TOD) IN KAWASAN BAKRIE NIRWANA RESIDENCE MULYA HARJA - Al Munawar, Muhammad Agil; Murtejo, Tedy; Rulhendri, Rulhendri; Chayati, Nurul (ASTONJADRO, 2021)
The regional development plan and integrated transportation network in the city of Bogor, especially in the Bogor Nirwana Residence Mulya Harja area, requires a plan for determining transit-based movements. The concept of transit oriented development (TOD) is a spatial engineering approach that focuses its development around transit points. The space developed in a transit-oriented area has the characteristics of high density, various mixes (updates) and a design area that is friendly to pedestrians and bicycle users. As for anticipating the emergence of transportation problems in the development of the TOD area, a study is carried out on the analysis of potential generation and attraction to find out how much movement is entering a zone or leaving a zone.to predict the amount of traffic pull generation to and from the TOD area development location. Data collection techniques include existing observations, traffic surveys and document review. The analysis of land use designation refers to the standards and regulations related to the development of transit-oriented areas, while the calculation of the generation of attraction uses the coefficient ofITE (Institute Transportation Engineers) Generation 9th. The results of the research are the level of conformity of the Basic Building Coefficient (KDB), Building Floor Coefficient (KLB) and Green Base Coefficient (KDH) on land use designation on the application of the TOD concept in the BNR area. The results were KDB with a preset rate of 64%, KLB with a percentage rate of 3.28 and KDH of 10%. In the calculation results of the movement generation obtained in the study area with a total of 2,118 (Trips / Hour), while for the results of the movement of the movement obtained in the study area with a total of 31,780 (trips/hour).